Quantifying Rock Slope Stability with Kinematic and Limit Equilibrium Methods for KM29 of Karak Highway, Malaysia - Nurul Afiffah Khairulazman,; Jestin Jelani,; Suriyadi Sujipto,; Zainuddin Md Yusoff,; Zuliziana Suif,; Mohd Rozi Umor, (International Journal of Integrated Engineering, 2025)
The stability of rock slopes has been of great interest to engineering geology studies in ensuring a safe and functional cut slope along highways. Kinematic analysis is widely used as an assessment tool for rock slope stability in Malaysia. This method uses a stereograph plot to identify potential failure modes based on geological discontinuities. However, it does not quantify any forces that could influence the potential failure. To address this limitation, the Limit Equilibrium Method (LEM) is employed to calculate the slope’s factor of safety, providing a more comprehensive stability assessment. In this study, both kinematic analysis and LEM were applied to evaluate the stability of a rock slope located at KM29 near the Gombak Toll Plaza, along the Karak Highway, Malaysia. Parameters such as discontinuities and mechanical properties were used to analyse the slope. The Schmidt rebound hammer was employed to evaluate the surface hardness of the rock. The average rebound values for slope sections G1, G2, and G3 were 62, 60, and 54, respectively. These values were then correlated with uniaxial compressive strength (UCS), yielding estimated strengths of 163.97 MPa for G1, 150.65 MPa for G2, and 113.98 MPa for G3. The shear strength test indicated an average cohesion value of 20.56 kPa and a friction angle of 56.79°, derived from four rock samples. Kinematic analysis, conducted using Rocscience Dips software, revealed that slope sections G1, G2, and G3 were susceptible to wedge and planar failures. In contrast, the factor of safety (FOS) determined by LEM, simulated using Slope/W, confirmed that all slope sections are stable, with FOS values exceeding 1.5. The integration of kinematic analysis and LEM should be considered essential for evaluating rock slope stability and reinforcing the final decision-making process.